Wound-healing evaluation of ointment from Stryphnodendron adstringens (barbatimão) in rat skin - Luzmarina Hernandes; Luciene Marques da Silva Pereira; Fabiana Palazzo; João Carlos Palazzo de Mello (Universidade de São Paulo, 2010)
This study evaluated the cicatrizant effect of an ointment containing 1% of the ethyl-acetate fraction extracted from the stem bark of "barbatimão" (Stryphnodendron adstringens), in wounds made in the skin of rats, after 4, 7 and 10 days of treatment. Control wounds were treated with a base ointment without extract. The proliferation of keratinocytes in the area of reepithelialization was evaluated by counting the number of epithelial cells that were blocked in metaphase by vincristine sulfate. The length of the reepithelialized margin and the contraction of the wound were measured. Topical application of the "barbatimão" ointment stimulated proliferation of the keratinocytes, but had no effect on the length of the epithelium or on the contraction of the wounds. Neste estudo, avaliou-se a atividade cicatrizante de uma pomada contendo uma fração acetato de etila 1% obtida de cascas de "barbatimão" (Stryphnodendron adstringens) em feridas excisionais na pele de ratos após 4, 7 e 10 dias de tratamento. Feridas controle foram tratadas com pomada base, sem extrato. A proliferação dos queratinócitos na área reepitelizada foi avaliada através da contagem do número de queratinócitos bloqueados em metáfase, pelo sulfato de vincristina. O comprimento da margem reepitelizada e a contração das feridas foram mensurados. As feridas tratadas com barbatimão apresentaram um maior número de mitoses do que aquelas tratadas com a pomada base, em todos os tempos avaliados. A aplicação tópica da pomada de "barbatimão" estimulou a proliferação epitelial contudo não teve efeito sobre a migração dos queratinócitos ou sobre a contração das feridas.